Evaluation of the Outcomes of Coronectomy Procedure versus Surgical Extraction of Lower Third Molars Which Have a High Risk for Inferior Alveolar Nerve Injury: A Systematic Review - Nedal Abu-Mostafa; Lulwah M. AlRejaie; Fahad A. Almutairi; Ruba A. Alajaji; Maram M. Alkodair; Nourah A. Alzahem (Hindawi Limited, 2021)
Background and Objectives. Surgical extraction of mandibular third molars (3rd M) may cause inferior alveolar nerve injury (IANI), whereas in coronectomy the crowns of 3rd M are removed, keeping the roots intact to avoid IANI. This study aims to review the literature which evaluated coronectomy effectiveness as an alternative for surgical extraction of 3rd M that have a high risk of trauma to the inferior alveolar canal. A computerized literature search was conducted on the databases PubMed, SCOPUS, and ScienceDirect to gather information regarding the coronectomy procedure from inception till June 5, 2020. A total of 97 articles were identified, and seven studies were finally included for conducting qualitative analysis: 3 randomized clinical trials and 4 clinical controlled trials. Cochrane Collaboration's tool was used for assessing risk of bias. Coronectomy procedures were performed on 15-171 teeth. In the control group, extraction procedures were done on 15-178 teeth. Results. No study reported permanent inferior alveolar nerve injury (p-IANI) regarding coronectomy; however, transient inferior alveolar nerve injury (t-IANI) was reported in 0-2.20% of successful coronectomy and 0-8% of failed coronectomy. Postextraction t-IANI ranged from 0% to 16.66% while p-IANI from 0% to 3.63%. In 5 studies, root migration occurred in 2% to 85.3% of cases and the distance rate was 2.33-3.43 mm at 6 months postoperatively; then the migration gradually decreased and stopped at 12 months. Conclusion. This systematic review revealed that coronectomy is an efficient alternative for the management of impacted 3rd M with a high risk of IANI. Patients who got antibiotics postcoronectomy procedures had lower infection rates than those who did not receive antibiotic therapy. We recommend further research on coronectomy with longer follow-up periods to assess the retained roots' long-term outcomes and to assess the effect of antibiotics administration on postcoronectomy infection rate. This systematic review is registered under number CRD42020198394.